2016
DOI: 10.1007/s11356-016-7850-3
|View full text |Cite
|
Sign up to set email alerts
|

Short residence duration was associated with asthma but not cognitive function in the elderly: USA NHANES, 2001–2002

Abstract: There has been a growing interest in how the built environment affects health and well-being. Housing characteristics are associated with human health while environmental chemicals could have mediated the effects. However, it is unclear if and how residence duration might have a role in health and well-being. Therefore, the aim of the present study was to investigate the associations among residence duration, common chronic diseases, and cognitive function in older adults in a national and population-based set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, despite there are many studies that showed the association between ADHD and allergic diseases and explained it genetically and physiologically, the number of studies that focused on ADHD-related cognitive dysfunctions was relatively small and showed inconsistent results. For example, some studies have reported that dysfunctions in concentration, selective attention, and psychomotor speed were related to AR [6-8], but con icting results also existed [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite there are many studies that showed the association between ADHD and allergic diseases and explained it genetically and physiologically, the number of studies that focused on ADHD-related cognitive dysfunctions was relatively small and showed inconsistent results. For example, some studies have reported that dysfunctions in concentration, selective attention, and psychomotor speed were related to AR [6-8], but con icting results also existed [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%